Smart Android tablet tracking system - Qian, Bingqing (2013)
Indoor positioning has been researched and developed significantly in the past few years because the applications used for tracking person or object in the indoor environment are increasing in importance and purposes. The outdoor positioning system is accurate and efficient due to the global satellite positioning systems (GPS), but applications should be capable of being able to perform indoor as well so that a larger target market could be hit. No single solution is available for affordable and accurate indoor positioning. Extended market analysis is required to tailor the user needs with the carefully weighed parameters such as accuracy, cost, privacy, coverage, speed etc.